2005
DOI: 10.1161/circulationaha.105.534271
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of Fgl-2/Fibroleukin in the Donor Modulates Immunologic Response and Acute Vascular Rejection in Cardiac Xenografts

Abstract: Background— Xenografts ultimately fail as a result of acute vascular rejection (AVR), a process characterized by intravascular thrombosis, fibrin deposition, and endothelial cell activation. Methods and Results— We studied whether targeted deletion of Fgl-2, an inducible endothelial cell procoagulant, (Fgl-2 −/− ) in the donor prevents AVR in a mouse-to-rat cardiac xenotransplantation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 46 publications
(36 reference statements)
3
42
0
Order By: Relevance
“…These proteins have been shown to exhibit coagulant and angiogenic activity, as well as immunoregulatory activity (1,2,30). Similar to other members of the fibrinogen superfamily, our laboratory has recently discovered (19) that FGL2 inhibits murine DC maturation and adaptive T cell immune responses, in addition to its role in innate immunity through its ability to activate the coagulation system (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins have been shown to exhibit coagulant and angiogenic activity, as well as immunoregulatory activity (1,2,30). Similar to other members of the fibrinogen superfamily, our laboratory has recently discovered (19) that FGL2 inhibits murine DC maturation and adaptive T cell immune responses, in addition to its role in innate immunity through its ability to activate the coagulation system (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…FGL2 was first cloned from human CTLs, and its protein structure deduced from the nucleotide sequence showed a high degree of homology to fibrinogen ␤ and ␥ subunits (3). FGL2 has been shown to play an important role in innate immunity as an immune coagulant expressed by activated reticuloendothelial cells (macrophages and endothelial cells) (4 -6) and has been implicated in the pathogenesis of several inflammatory disorders, including viral hepatitis (7)(8)(9)(10), allo-and xenograft rejection (11)(12)(13), and cytokine induced fetal loss (14,15). In a previous report (13), we showed that Ab to FGL2 ameliorated allograft rejection.…”
mentioning
confidence: 99%
“…Fgl2 functions as a strong prothrombinase which directly cleaves prothrombin to thrombin leading to fibrin deposition in the absence of factor Ⅶ or factor Ⅹ [10] . The direct prothrombinase activity of fgl2 is implicated in the pathogenesis of several inflammatory disorders including fulminant hepatitis and severe hepatitis, alloand xeno-graft rejection [4,11,12] . Furthermore, its role is also evidenced in murine and human cytokine induced fetal loss [5,[13][14][15] and neonatal death from contractile dysfunction and rhythm abnormalities during embryonic and postnatal development [16] .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several target gene candidates for transgenic expression (e.g., CD39, TFPI, thrombomodulin, hirudin, CD73), or knock-out (e.g., Tissue Factor, PAR3, PAR4, Fgl-2) in pig tissues have been identified. Encouraging results, although only obtained in vitro 66 and in small animal models, [67][68][69][70][71] have provided a basis for the future genetic manipulation of porcine organs possibly able to overcome thrombotic events that compromise xenograft survival.…”
Section: Regulatory and Ethical Frameworkmentioning
confidence: 99%